Teaching quality and performance among experienced teachers in Malaysia - Abd Hamid, Siti Rafiah; Syed Hassan, Sharifah Sariah; Ismail, Nik Ahmad Hisham (Edith Cowan University., 2012)
The role of teachers has evolved from merely being teacher-centered to one that is student centered and the skills required for a quality teacher are changing too. Assessing teachers’ effectiveness is not just examining students’ achievements or students’ perceptions of their teachers’ attributes but it includes a host of other contributing factors. A careful examination of the teaching concepts, one as a form of “labor and profession” (Firestone & Bader, 1991); or the other as a “craft and art” (Grimmett & MacKinnon, 1992) indicated that it largely involves teachers’ cognitive ability and interpersonal skills (soft skills) which enhance teachers’ performance in the classroom. Furthermore, the National Framework for Professional Standards (MCEETYA, 2003) has outlined that teachers’ professional value (quality and professional knowledge and skills) will impact students’ learning. Based on these concepts, this study investigated a teacher effectiveness model. The study also measured the teachers’ cognitive ability (skills of assessment and evaluation, Information Technology (IT) skills, and co-curricular knowledge) and the teachers’ personality or interpersonal skills (soft skills). The respondents were experienced teachers working in Malaysia. A set of questionnaires with 120 questions were constructed by the researchers and were administered among 2000 school teachers from different types of schools. However, only 1366 completed questionnaires were analyzed while 634 responses were removed due to incomplete data. Utilizing the structural equation model (SEM), this study attempted to ascertain the validity of the structural model where teachers’ cognitive abilities and personalities predict teachers’ performances. The results indicated a model fit with both teachers’ cognitive abilities and personality predicting effective classroom management. Sound personality alone is insufficient in terms of enhancing the teachers’ commitment and responsibilities towards their students unless it is complemented by the teachers’ cognitive competency (cognitive abilities).